MICROBIOLOGICAL AND PHYSICOCHEMICAL ANALYSIS OF HOMEMADE FRESH MILK MARKETED IN ANÁPOLIS - GO - Costa, Gabriela Macedo; Costa de Oliveira, Ricardo; Luchetti, Rubia de Pina (CIPEEX, 2025)
Title: Microbiological and Physicochemical Analysis of Homemade Fresh Milk Marketed in Anápolis - GO Objective: To analyze the microbiological and physicochemical quality of homemade fresh milk sold in the Anápolis - GO region, focusing on the detection of Salmonella spp. Justification: Raw milk consumption is common in family and rural settings, often without proper sanitary inspection, posing a public health risk due to potential contamination with pathogenic microorganisms. Methodology: Sampling: Milk samples collected over one year. Physicochemical analyses: pH, titratable acidity, density, fat content, protein content, cryoscopy, and water activity. Microbiological analyses: Mesophilic bacteria count, total and thermotolerant coliforms, molds and yeasts, and detection of Salmonella spp. using selective media and confirmatory tests. Methodological references: AOAC, Embrapa, MAPA, and ANVISA. Data comparison: Results will be compared with MAPA Normative Instruction No. 76/2018 and ANVISA Normative Instruction No. 161/2022. Expected Results: Variations in physicochemical parameters among samples. Presence of Salmonella spp. in some samples. Evidence of deficiencies in milking and milk preservation practices. Impact and Applications: The findings may support educational initiatives and hygienic-sanitary control strategies, promoting safer artisanal milk production and consumption.